Consistency in patient-reported outcome measures after total knee arthroplasty using patient-specific instrumentation: a 5-year follow-up of 200 consecutive cases - Schoenmakers, Daphne A. L. (Knee Surg Sports Traumatol Arthrosc, 2017)
PURPOSE: The purpose of this study was to evaluate the 5-year follow-up results of the first 200 total knee arthroplasties (TKA) performed by one high-volume surgeon, using patient-specific information (PSI). To date, there has been no other research into the mid-term follow-up of TKA performed using PSI. MATERIALS AND METHODS: A total of 184 consecutive patients (200 TKA) were evaluated. Outcome measures included implant survival rate, adverse events, and the following patient-reported outcome measures (PROMs); Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Oxford Knee Score (OKS), Pain Visual Analogue Score (VAS) and EuroQol-5D Score (EQ-5D). RESULTS: Revision surgery was performed for late secondary prosthetic joint infection (n = 1, total revision), aseptic loosening (n = 1, tibial component revision), instability (n = 1, isolated polyethylene insert exchange), and polyethylene insert breakage (n = 1, isolated polyethylene insert exchange). Other adverse events were as follows: debridement, antibiotics and implant retention for early prosthetic joint infection (n = 1), surgical debridement for haemarthrosis (n = 1), superficial wound infection (n = 2), thromboembolic events (n = 2), compartment syndrome (n = 1), and nerve injury (n = 2). All median outcome scores for patient reported outcome measures at 5 years improved significantly compared with the preoperative values (p ≤ 0.05). Median outcome scores were not significantly different between 1- and 5-year moments of follow-up, except for a significant decrease of EQ-VAS (p ≤ 0.05) between these two follow-up moments. CONCLUSION: PROMs are consistent for 5-year follow-up of TKA using PSI. After 5 years of follow-up, revision surgery for any reason occurred in four patients (2%). LEVEL OF EVIDENCE: III.